2010
DOI: 10.1007/s00705-010-0706-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological survey of hepatitis E virus infection among domestic pigs in Inner Mongolia, China

Abstract: To evaluate the prevalence and characteristics of swine hepatitis E virus (HEV) infection in Inner Mongolia, China, serum samples obtained from 356 2- to 4-month-old pigs on 14 farms in Inner Mongolia were tested for the presence of anti-HEV antibodies and HEV RNA. Overall, 186 pigs (52%) tested positive for anti-HEV antibodies, while 30 pigs (8%) had detectable HEV RNA levels. The 30 HEV isolates recovered from the viremic pigs were phylogenetically classified into genotype 4 and differed from each other by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In a previous study involving putative HEV G4 virulence determinants, one potential determinant is located in each of the 5ʹ-UTR and 3ʹ-UTR, 3 and 12 determinants are detected in ORF1 and ORF2, respectively, and two determinants are found in the junction [14]. Thus far, at least nine subtypes (4a–4i) of G4 HEV isolates have been identified; numerous new subgenotypes have been reported in humans and pigs [1518]. In one of our previous surveys, at least four subgenotypes (4c, 4d, 4b, and a new subgenotype) are prevalent in Yunnan Province.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study involving putative HEV G4 virulence determinants, one potential determinant is located in each of the 5ʹ-UTR and 3ʹ-UTR, 3 and 12 determinants are detected in ORF1 and ORF2, respectively, and two determinants are found in the junction [14]. Thus far, at least nine subtypes (4a–4i) of G4 HEV isolates have been identified; numerous new subgenotypes have been reported in humans and pigs [1518]. In one of our previous surveys, at least four subgenotypes (4c, 4d, 4b, and a new subgenotype) are prevalent in Yunnan Province.…”
Section: Discussionmentioning
confidence: 99%
“…In France, 31% (95% CI 24–38) of the slaughter-aged pigs in 2011 were found HEV seropositive [5]. Similarly, Jinshan et al detected 52% of sampled pigs positive for anti-HEV antibodies in Mongolia [15]. Crossan et al separately tested the presence of the different types of anti-HEV antibodies in Scotland and reported that, of 176 serum samples tested, 29% ( n  = 51) were anti-HEV IgG-positive, 36.9% ( n  = 65) anti-HEV IgA-positive and 29% ( n  = 51) anti-HEV IgM-positive.…”
Section: Hev Prevalence In Farmed Pigsmentioning
confidence: 99%
“…The risk factors for a high HEV seroprevalence were mainly related to (1) farm characteristics and (2) farming practices. The farming scale (medium-size and family-scale farms, linked to the number of pigs and sows) was identified as a risk factor related to HEV seroprevalence [15, 18, 20, 21]. It was also shown that HEV seroprevalence was significantly higher in organic farms than in conventional ones [22].…”
Section: Hev Prevalence In Farmed Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…Farm‐level observational studies have highlighted husbandry practices in terms of hygiene, biosecurity and rearing conditions as pivotal factors favouring HEV spread on farms (e.g. farm size, mingling practices, origin of drinking water, presence of a hygiene lock) (Hinjoy et al, ; Jinshan, Manglai, Takahashi, Nagashima, & Okamoto, ; Li et al, ; Walachowski et al, ). Between‐farm pig movements and the contact network topology have also been found to influence the epidemiological HEV situation of farms (Salines, Andraud, & Rose, ).…”
Section: Introductionmentioning
confidence: 99%